The Effect of Islamic Corporate Governance and Maqashid Sharia Index on Islamic Social Reporting - Qonitatun Luthfiyah (Yayasan Az Zukhruf Cendikia, 2024)
Purpose – This study aims to examine, analyze, and obtain empirical evidence regarding the effect of Islamic Corporate Governance and Maqashid Sharia Index on Islamic Social Reporting of the Largest Islamic Banks in the World. From the results of the study it is known that the Islamic Corporate Governance variable significantly affects Islamic Social Reporting, while the Maqashid Sharia Index variable does not significantly affect Islamic Social Reporting. Design/methodology/approach – This study uses secondary data in the form of annual reports or sustainability reports and other information of Islamic Banks. The samples in this study were the 10 Largest Islamic Banks in the World selected using purposive sampling technique. The research implementation time was for 6 periods from 2017 - 2022. Research using panel data with panel regression models and data processing software using Eviews. Findings – This research is expected to provide information related to Islamic social reporting and provide benefits in making the right decisions and can be used as a reference for further research. Research limitations/implications – This study has several limitations that should be considered when interpreting the results. First, the sample size is limited to the 10 largest Islamic banks in the world, which may not fully represent the diversity of Islamic banks globally. Implications for future research include the need to expand the sample size to include a more diverse range of Islamic banks, both in terms of size and geographic spread, as well as extending the study period to capture more longitudinal data. Researchers could also explore qualitative methods to gain a deeper understanding of the motivations behind Islamic Social Reporting and the role of different governance frameworks in influencing these disclosures. Moreover, the non-significant effect of the Maqashid Sharia Index on ISR suggests a need for further investigation into the relationship between Islamic principles and reporting practices in Islamic financial institutions.